A mitochondria-targeted fluorescent probe for monitoring of H2O2 and polarity/viscosity-related microenvironmental changes in food mycotoxin- and environmental contaminant-induced hepatotoxicity - Zibo Zhai; Jia Huang; Xijian Wang; Hailin Zhang; Min Deng; Qiqi Wen; Jingting Fang; Lizi Liu; Ziyang Ding; Dan Cheng; Longwei He; Songjiao Li (Journal of Environmental Chemical Engineering, 2026)

Preferences for different prey and molecular mechanisms of feeding regulation in Neptunea arthritica cumingii Crosse - Wenhui Gu; Junxia Mao; Xubo Wang; Fengxiao Lü; Ping He; Linxuan Cai; Longwei Dai; Menghao Jia; Ying Tian; Zhenlin Hao (Journal of Oceanology and Limnology, 2026)

Reactive oxygen species-scavenging, overloaded calcium-inhibiting, neuroregeneration-promoting polydopamine functionalized magnesium oxide nanoparticle-integrated hydrogel accelerates spinal cord injury repair - Feng Wei; Xu Gao; Wen Yang; Keni Yang; Zhifeng You; Longwei Li; Hongchao Zhang; Lulu Zhang; Yuxuan Ji; Yan Zhuang; Jianwu Dai; He Shen (Chemical Engineering Journal, 2025)

The size-variation of microplastics alters plant nitrogen uptake by regulating soil gross nitrogen transformation rates - Xiaoqian Dan; Mengqiu He; Yuhong Wen; Longwei Meng; Meirong Huang; Shending Chen; Qilin Zhu; Yanzheng Wu; Shuirong Tang; Ahmed S. Elrys; Zucong Cai; Jinbo Zhang; et al. (Soil Biology and Biochemistry, 2025)

An efficient three-dimensional mesh quality optimization method based on gradient-enhanced probabilistic model - Longwei Deng; Junhui Yin; Qing He; Xinyu Cao; Chaoyang Zhang; Junhao Cui; Bin Li (Computer Physics Communications, 2025)

Machine learning-enhanced multifunctional graphene electronic patches for gesture recognition and human-robots ultrasound encryption communication - Hao Sun; Sheng-Yuan Xia; Renzhi He; Longwei Li; Hongxiang Xue; Lu-Qi Tao; Fuchun Sun (Chemical Engineering Journal, 2025)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Imaging peroxynitrite in endoplasmic reticulum stress and acute lung injury with a near-infrared fluorescent probe - Ke Yang; Ying Liu; Min Deng; Peipei Wang; Dan Cheng; Songjiao Li; Longwei He (Analytica Chimica Acta, 2024)

Assessing the efficiency of ozone-based advanced drinking water treatment processes in removing antibiotics and antibiotic-resistant genes: Pilot-scale research - Gezi Li; Bolin Li; Mingxing Yu; Jun Wang; Longwei Jiang; Ying Yu; Xueni Sha; Xiaoman He; Zhi Zhou (Journal of Water Process Engineering, 2023)

Aggregation enhanced FRET: A simple but efficient strategy for the ratiometric detection of uranyl ion - Dan Wang; Li-Jie Zhang; Ming-Hui Liu; Fang-Fang Du; Ze-Ya Shen; Longwei He; Li-Li Wang (Journal of Hazardous Materials, 2023)

Development of a Golgi-targeted superoxide anion fluorescent probe for elucidating protein GOLPH3 function in myocardial ischemia-reperfusion injury - Ao Li; Yalan Liu; Labapuchi; Zhe Chen; Songjiao Li; Rongbin Zhong; Dan Cheng; Linxi Chen; Longwei He (Analytica Chimica Acta, 2023)

Construction of HClO activated near-infrared fluorescent probe for imaging hepatocellular carcinoma - Songjiao Li; Peipei Wang; Ke Yang; Ying Liu; Dan Cheng; Longwei He (Analytica Chimica Acta, 2023)

A mitochondrial-targeted near-infrared fluorescent probe for visualizing the fluctuation of hypochlorite acid in idiopathic pulmonary fibrosis mice - Songjiao Li; Peipei Wang; Ying Liu; Ke Yang; Rongbin Zhong; Dan Cheng; Longwei He (Analytica Chimica Acta, 2023)

An ICT-Based Hydrogen Sulfide Sensor with Good Water Solubility for Fluorescence Imaging in Living Cells - Qiuyan Xu; Longwei He; Haipeng Wei; Weiying Lin (Journal of Fluorescence, 2018)

Transdermal Adhesive Patches Loaded with Ketoprofen Evaluated by Dynamic Detection of Percutaneous Absorption - Menglin Wang; Longwei Li; Junxia Xie; Yinghua Sun; Guixia Ling; Zhonggui He (AAPS PharmSciTech, 2017)